Multi-omics analysis links NFKB1 activation to poor immunosuppressive therapy response in acquired aplastic anemia - Nianbin Li; Ting Wang; Boyi Wang; Rong Fu (Hematology)
Objectives: Acquired aplastic anemia (AA) is a bone marrow failure syndrome whose pathogenesis remains incompletely understood. This study aimed to explore the genetic determinants underlying AA and identify potential therapeutic targets.Methods: We integrated summary data – based Mendelian randomization (SMR) and colocalization analysis to identify genes causally linked to AA. Key candidates were validated using single-cell RNA sequencing to assess their expression and pseudotime dynamics. We explored B-cell – mediated cell communication related to immunosuppressive therapy response. Serum expression of candidate genes was validated and correlated with clinical outcomes.Results: SMR analysis identified 28 genes significantly associated with AA, among which NFKB1 emerged as a central regulatory factor. scRNA-seq data confirmed NFKB1's differential expression in B cells and its dynamic regulation during disease progression. Discussion and conclusion: This study is the first to comprehensively characterize the role of NFKB1 in the pathogenesis of AA through integrated multi-omics analysis and providing novel insights for the development of targeted interventions.